Analysis of the Effect of Remote Audit, Professional Scepticism and Going Concern Assessment on Audit Quality During the Covid-19 Pandemic : Case Study at Public Accountant Firm in Bali Province - D Angeliney She Maharaja; Ida Bagus Anom Yasa; Paulus Subiyanto (Journal of Applied Sciences in Accounting, Finance, and Tax, 2022)
Audit quality plays an important role in ensuring the fairness of financial statements to improve decision- making by interested parties. However, there were several cases of suspension of public accountants' licenses in recent years reflecting the low audit quality. The existence of the Covid-19 Pandemic which causes business economic instability conditions and changes in the auditor work mechanism make audit quality increasingly need to be considered. Remote audit during the pandemic cause limited scope for inspection, availability of technological tools, and weak document validity. Fraud increasing is also note for auditors to sharpen their professional skepticism. Another thing in supporting audit quality during the pandemic is the accuracy of going concern assessment which can provide an overview of the company's sustainability. This study aims to analyze and explain the effect of remote audit, professional skepticism, and going concern assessment on audit quality during the Covid-19 Pandemic at Public Accountant Firms in Bali Province. The population in this study are 115 auditors in 17 Public Accountant Firms registered in IAPI Bali with a total of 69 respondents based on convenience sampling method. Primary data were obtained from questionnaires and analyzed with Partial Least Square (PLS) through SmartPLS 3.0 application with a significance level of 5%. The results showed that remote audit, professional scepticism, and going concern assessment have a positive and significant impact on audit quality during the Covid-19 Pandemic at Public Accountant Firms in Bali Province.